Voices of Wisdom: Geriatric Interviews on Self-Management of Type 2 Diabetes in the United States—A Systematic Review and Metasynthesis - David F. Lo; Ahmed Gawash; Kunal P. Shah; Jasmine Emanuel; Brandon Goodwin; Don D. Shamilov; Gaurav Kumar; Nathan Jean; Christian P. White (Journal of Diabetes Research)
This review is aimed at unraveling the intricacies of diabetic self-management among geriatric people, drawing on current insights and understanding the complex paths geriatric people navigate. A wide search was conducted in health-oriented databases, including CINAHL, Embase, PsycINFO, MEDLINE, PubMed, Web of Science, and Cochrane Library, while gray literature was excluded. The search combined keywords and subject headings, focusing on the geriatric population, diabetes, self-management, and qualitative research. A three-tiered screening process was employed, with titles and then abstracts initially reviewed. Full-text analysis followed, with disagreements resolved among reviewers. In total, there were 248 participants included across these eight studies. Positive attitudes and perceptions were found to play a significant role in optimizing diabetes self-care outcomes. Support from family and friends was identified as crucial for self-care, while healthcare professionals often lacked adequate support and encouragement. Participants emphasized the importance of listening to their bodies and acknowledging hidden issues. These themes collectively highlight the multifaceted aspects of diabetes self-care and the impact of various factors on the self-management experiences of geriatric individuals with diabetes. The goal of this review is not to objectify self-management as a treatment strategy but to emphasize the importance of cultivating positive attitudes, respecting individual values, and addressing cultural and ethnic differences in healthcare practices to enhance self-management in this population. By embracing cultural diversity, understanding barriers, and respecting individual values, healthcare professionals and policymakers can improve the quality of life for the geriatric population living with diabetes.